Исследование взрывобезопасности полимерных ограничителей перенапряжений 3,3 кВ постоянного тока для тяговой сетижелезнодорожного транспорта - Шумилов, Юрий Николаевич; Бондаренко, Владимир Иванович (Национальный технический университет "Харьковский политехнический институт", 2019)
Проведены испытания полимерных образцов ОПН-3,3 кВ в эксплуатационных условиях на оборудовании действующей подстанции, при токах короткого замыкания 8,3 кА и времени воздействия тока 0,02 с, близких по величине к рекомендуемым стандартом IEC 60099-4:2014 значениям. Испытано 8 шт. ограничителей перенапряжений. Каркас, в котором были заключены варисторы, выполнялся либо путём намотки стеклопластиковой ленты на варисторную колонку, либо из стержней, расположенных в виде "беличьей клетки", либо в виде стеклопластиковой трубы с отверстием для выброса газов при коротком замыкании внутри ОПН. Образцы показали вполне удовлетворительную способность выдерживать большие импульсные токи без разлёта опасных для персонала и окружающего оборудования фрагментов. Полимерные конструкции, каркас которых выполнен сплошной намоткой, требуют усиления зоны соединения каркаса с электродами для исключения вылета электродов при скоплении газов при коротком замыкании внутри корпуса ОПН. Для таких конструкций требуется введение в программу приёмо-сдаточных испытаний дополнительной проверки на механическую прочность в продольном направлении с заранее установленной нормой прочности.

In the testing laboratories of Ukraine, there is no high-voltage equipment of the necessary energy for testing surge arresters for explosion safety, which does not allow to estimate this indicator at the stage of development of prototypes. In view of this test, the polymer prototypes of the DC surge arresters in polymer case (SAp) 3.3 kV were tested under the operating conditions of the equipment of the operating substation with short-circuit currents of 8.3 kA and a current time of 0.02 seconds, close to the recommended by Standard of IEC 60099-4:2014 values. 8 samples of surge arresters were tested. A sample of the surge arrester was mounted on one of the metal supports at a height of 5.5 m located in the substation and connected to the 3.3 kV traction substation buses through disconnectors and a high-speed switch. After the short-circuit breaker was closed through a column with a pre-punched or shunted copper wire varistor, a short-circuit current flowed to form an electric arc inside the arrester samples. During the tests video samples were recorded using a video recorder installed in close proximity to the test sample. The frame of the SAp samples in which the varistors were enclosed was performed either by winding the fiberglass tape on a varistor column, or fromrods arranged in the form of a squirrel cage, or in the form of a fiberglass tube with a hole for gas ejection during a short circuit inside the SAp. The destruction of the hull occurred without scattering of the fragments in seven cases from the eight samples tested. In seven samples, a local rupture of the silicone shell occurred in the varistor zone, a gas ejection and an arc discharge occurred through this gap. The exception was sample No. 2, made by a continuous winding of a glass-banding tape on a varistor column, in which, during the explosion, the upper electrode exploded with the simultaneous expansion of fragments of the varistor in a radius of 3-5 m. Due to the white smoke accompanying the explosion, it was not possible to fix on the frame whether the arc output from the case to the outside, despite the fact that on the next frame (in 33 ms.) the arc was no longer fixed. In the tests of eight of the presented designs, none of them ignited the hull. If the tests were carried out on the surge arresters assembled with pre-punched varistors (electrothermal breakdown), the varistors during the tests split, remaining inside the frame. From the action of the arc in the contact zone of the aluminum electrodes with varistors, a deep burn-out of the electrodes was observed, in some cases, the burnup was up to 7 mm deep and up to 8 mm wide. If the varistors were shunted by a copper wire, they remained intact. If the varistors were shunted by a copper wire, they remained intact and melting and burning out a part of the aluminum electrodes in the area of connection with the copper wire were smaller sizes. The samples showed a completely satisfactory ability to with stand large pulse currents without dispersing dangerous fragments for personnel and surrounding equipment. However, polymer designs, the frame of which is made by continuous winding, require reinforcement of the connection zone of the carcass with electrodes to exclude the break-out of electrodes during the accumulation of gases during a short circuit inside the shell of the SAp. For such designs, an additional test for mechanical strength in the longitudinal direction with a predetermined norm is required in the acceptance test program.
Investigation of explosion safety of DC polymer surge arresters 3.3 kV for traction network of railway transport.
Keywords: электрооборудование тяговых устройств; защита от перенапряжений; ограничители перенапряжений; методика испытаний; взрывное разрушение; разлёт фрагментов; direct current; overvoltage protection; explosion safety; test procedure; explosive destruction; fragment separation